Providing Restitution Rights For Child Victims Of Sexual Violence Outside The Prosecutor's Demands - Artanti, Talita Dinda; Somawijaya, Somawijaya; Ramdan, Ajie (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
Although sexual violence often occurs against underage children, not many people understand or are sensitive to this issue. They often perceive it merely as a moral offense rather than a crime against humanity, resulting in repeated victimization of the survivors. One of the efforts that can be made to protect and restore the rights of child victims is through obtaining restitution. However, the implementation and fulfillment of restitution rights are not fully realized in all cases of sexual violence against children. This can happen because there is no obligation for public prosecutors to include restitution in their demands and there is no forced effort to ensure restitution rights. Nevertheless, restitution is a right that should be granted to the child victims, and its application should be maximized in Indonesia's criminal justice system. Judges should rule for additional punishment in the form of restitution even without a request, as restitution is often overlooked. This uncertainty in the legal process regarding restitution implementation does not provide a solution for the loss of restitution rights for child victims of sexual violence. Therefore, other efforts must be undertaken to ensure that child victims of sexual violence receive their rightful restitution.